Pengaruh Kesadaran Wajib Pajak, Pengetahuan Pajak,Sanksi Perpajakan Dan Akuntabilitas Pelayanan PublikPada Kepatuhan Wajib Pajak Kendaraan Bermotor DanBiaya Balik Nama Kendaraan Bermotor Di Kantor Bersama Samsat Klaten - Chasanah, Octariana Eka Nur, Drs. Muhammad Abdul Aris, M.Si (2016)
The purpose of this study was to determine the effect of awareness of taxpayers , tax knowledge , tax penalties and accountability of public services on taxpayer compliance costs of motor vehicles and motor vehicle ownership transfer in the Office of the Joint SAMSAT Klaten . This study uses a quantitative method using primary data obtained from questionnaires. The population in this study is the Compulsory Motor Vehicle Tax Offices listed in Shared SAMSAT Klaten. The number of samples in this study were 100 taxpayers. Methods of sample collection using accidental sampling technique. The analytical tool used include validity and reliability test, normality test, multicollinearity, heteroscedasticity test, multiple linear regression, F test, the coefficient of determination R, and t test . The results showed that Adjusted R2 values obtained 0.291 which means that 29.10 % rate of motor vehicle tax compliance is influenced by the level of awareness of taxpayers, tax knowledge, tax penalties and accountability of public services. The remaining 70.90 % influenced by variables outside the model. T test results showed that the influence of awareness of taxpayers, tax knowledge, tax penalties and accountability of public service a positive effect on tax compliance vehicles.